ATTRAITS DU MECANISME DE DEVELOPPEMENT PROPRE POUR LA TUNISIE - Bernard, Alain; Talbi, Besma; Vielle, Marc (مركز الدراسات والابحاث الاقتصادية والاجتماعية, 2010)
The paper aims at measuring the benefit for the Tunisian economy of a participation to the Clean Development Mechanism, one of the flexibility Systems provided by the Kyoto protocol. Starting from a detailed -technical and economic- analysis of the most promising projects that are eligible to the mechanism, the study consists in the various relevant simulations with a world Computable General Equilibrium model, GEMINI-E3, in a version specifically designed to fully cope with the data on the Tunisian economy. \ A comparison is made with a scenario taking into account a larger participation of non-Annex B countries, such as China and India, which may obtain a large share of the projects through very low abatement costs in the present situation.
Keywords: التنمية الاقتصادية -- التنمية المستدامة -- حماية البيئة -- تونس